Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
x3-12x-4x2+27
=(x3+27)-(12x+4x2)
=(x+3)(x2-3x+9)-4x(x+3)
=(x+3)(x2-3x+9-4x)
=(x+3)(x2-7x+9)
\(x^3-12x-4x^2+27\)
\(=x^3+3x^2-7x^2-21x+9x+27\)
\(=x^2\left(x+3\right)-7x\left(x+3\right)+9\left(x+3\right)\)
\(=\left(x+3\right)\left(x^2-7x+9\right)\)
Đặt \(x^2-3x-1=a\), ta có:
\(a^2-12a+27=a^2-9a-3a+27=a\left(a-9\right)-3\left(a-9\right)=\left(a-9\right)\left(a-3\right)\)
\(=\left(x^2-3x-1-9\right)\left(x^2-3x-1-3\right)=\left(x^2-3x-10\right)\left(x^2-3x-4\right)\)
Mà \(x^2-3x-10=x^2-5x+2x-10=x\left(x-5\right)+2\left(x-5\right)=\left(x-5\right)\left(x+1\right)\)
và \(x^2-3x-4=x^2+x-4x-4=x\left(x+1\right)-4\left(x+1\right)=\left(x+1\right)\left(x-4\right)\)
\(\Rightarrow\left(x^2-3x-1\right)^2-12\left(x^2-3x-1\right)+27=\left(x-5\right)\left(x-4\right)\left(x+1\right)\left(x+2\right)\)
\(^{=x^3-3x^2+5x^2-15x+9x-27}\)
\(=x^2\left(x-3\right)+5x\left(x-3\right)+9\left(x-3\right)\)
\(=\left(x-3\right)\left(x^2+5x+9\right)\)
\(x^3+2x^2-6x-27\)
\(=x^3+5x^2+9x-3x^2-15x-27\)
\(=x\left(x^2+5x+9\right)-3\left(x^2+5x+9\right)\)
\(=\left(x-3\right)\left(x^2+5x+9\right)\)
ts cld b lv ag
81-(x2+6x)2
=92-(x2+6x)2
=(9+x2+6x)(9-x2-6x)
=(x+3)2(9-x2-6x)
27-64a3
=33-(4a)3
=(3-4a)[32+3*4a+(4a)2]
=(3-4a)( 9+12a+16a2)
Ta có : x^2 + x - 6
= x^2 + 3x - 2x - 6
= x ( x + 3 ) - ( 2x + 6 )
= x ( x + 3 ) - 2 ( x + 3 )
= ( x - 2 ) ( x + 3 )
Ta có : x6 - y6
\(=\left(x^3\right)^2-\left(y^3\right)^2\)
\(=\left(x^3-y^3\right)\left(x^3+y^3\right)\)
\(=\left(x-y\right)\left(x^2+xy+y^2\right)\left(x+y\right)\left(x^2-xy+y^2\right)\)
x6-y6=(x3)2-(y3)2=(x3-y3)(x3+y3)
=(x-y)(x2+xy+y2)(x+y)(x2-xy+y2)
đến đây bạn tự làm tiếp nha
a) \(x^2\left(x-3\right)+27-9x=0\)
\(x^2\left(x-3\right)+9\left(3-x\right)=0\)
\(x^2\left(x-3\right)-9\left(x-3\right)=0\)
\(\left(x^2-9\right)\left(x-3\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x^2-9=0\\x-3=0\end{cases}}\Rightarrow\orbr{\begin{cases}x^2=9\\x=3\end{cases}}\Rightarrow\orbr{\begin{cases}x=3\\x=3\end{cases}}\Rightarrow x=3\)
vay \(x=3\)
a) \(x^2-4x+3\)
= \(x^2-3x-x+3\)
\(=\left(x^2-3x\right)-\left(x-3\right)\)
\(=x\left(x-3\right)-\left(x-3\right)\)
\(=\left(x-1\right)\left(x-3\right)\)
a)\(x^2-4x+3=x^2-3x-x+3=x\left(x-3\right)-\left(x-3\right)=\left(x-3\right)\left(x-1\right)\)
b)\(x^2+x-6=x^2+3x-2x-6=x\left(x+3\right)-2\left(x+3\right)=\left(x-2\right)\left(x+3\right)\)
c)\(x^2-5x+6=x^2-2x-3x+6=x\left(x-2\right)-3\left(x-2\right)=\left(x-3\right)\left(x-2\right)\)
d)\(x^4+4=x^4+4x^2+4-4x^2=\left(x^2+2\right)^2-\left(2x\right)^2=\left(x^2-2x+2\right)\left(x^2+2x+2\right)\)
ta có: x6 +27=(x2)3 +33
=(x2+3)(x4 - 3x2 +9)